Pengaruh Jumlah Simpanan dan Jumlah Pinjaman Anggota terhadap Sisa Hasil Usaha (SHU) pada Koperasi Pegawai Universitas Muhammadiyah Sukabumi - Lena Agustin (ECONEUR (Journal of Economics and Entrepreneurship), 2022)
The government has expressly stipulated that within the framework of national development, cooperatives must become the backbone and vessel for the people’s economy, this government policy is in accordance with the contents of the 1945 Constitution article 33 paragraph 1 which states that the economy is structured as a joint venture based on the principle of kinship. This study aims to determine the effect of the amount of saving and the number of loans of members on the remaining result of operations at the Muhammadiyah University of Sukabumi Employee Cooperative from 2008 to 2010. The variables used in this study are the amount of loans as independent variables and the residual income business as the Dependent Variable. The method used in descriptive associative method based on the analysis that has been done, the result is that partially saving and Loans have an effect on remaining operating result. And testing simultaneously using the ftest then found the result, namely Fcount 91,634 > Ftable 3.30. then HO is accepted. Which means that the independent variables in this case Savings and Loans jointly have an influence on the Remaining Result of Operations at the Muhammadiyah University of Sukabumi Employee Cooperative.